Flavor science in the context of research on electronic cigarettes - Hayes, John E.; Baker, Allison N. (Frontiers in Neuroscience, 2022)
Thousands start smoking or vaping daily, despite long-standing efforts by public health authorities to curb initiation and use of nicotine containing products. Over the last 15 years, use of electronic nicotine delivery systems has increased dramatically, with a diverse range of products on the market, including pod-based, disposable, and refillable electronic cigarettes (eCigs). Originally intended for harm reduction and smoking cessation, eCigs may encourage nicotine use among never smokers, given the vast range of appealing flavors that are available. To better understand abuse liability and to facilitate appropriate regulations, it is crucial to understand the science of flavor, and flavor perception within the context of eCig use. Here, we (a) provide a brief primer on chemosensory perception and flavor science for addiction and nicotine researchers, and (b) highlight existing some literature regarding flavor and nicotine use, with specific attention given to individual differences in perception, and interaction between different sensory modalities that contribute to flavor. Dramatic increases in use of eCigs highlights the importance of flavor science in contemporary addiction research, both with regards to public health and regulatory efforts. Other recent work summarizes findings on flavored e-liquids and eCig use, but none have focused explicitly on chemosensory processes or flavor perception as they relate to appeal and use of such products. We argue flavor science needs to be considered as perceptual and behavioral phenomena, and not merely from analytical, toxicological and pharmacological perspectives; we help address this gap here.